Mechanical behavior of bilayered small-diameter nanofibrous structures as biomimetic vascular grafts. (July 2016) - Montini-Ballarin, Florencia; Calvo, Daniel; Caracciolo, Pablo C.; Rojo, Francisco; Frontini, Patricia M.; Abraham, Gustavo A.; V. Guinea, Gustavo
Abstract: To these days, the production of a small diameter vascular graft (<6 mm) with an appropriate and permanent response is still challenging. The mismatch in the grafts mechanical properties is one of the principal causes of failure, therefore their complete mechanical characterization is fundamental. In this work the mechanical response of electrospun bilayered small-diameter vascular grafts made of two different bioresorbable synthetic polymers, segmented poly(ester urethane) and poly(L -lactic acid), that mimic the biomechanical characteristics of elastin and collagen is investigated. A J-shaped response when subjected to internal pressure was observed as a cause of the nanofibrous layered structure, and the materials used. Compliance values were in the order of natural coronary arteries and very close to the bypass gold standard-saphenous vein. The suture retention strength and burst pressure values were also in the range of natural vessels. Therefore, the bilayered vascular grafts presented here are very promising for future application as small-diameter vessel replacements. Graphical abstract: Highlights: Electrospun biomimic bilayered small-diameter vascular grafts were investigated. A J-shaped response under internal pressure was obtained. Compliance, suture strength and burst pressure are in the order of human vessels. The bilayered vascular grafts are promising as small-diameter vessel replacements.